Traditional Indian Knowledge System and Practices: A Sociological Study (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
Sociology refers to the study of society its structures, interactions, relationships and process that influence human behavior. It seeks to understand how societal norms, values, institutions shape individuals actions and collective phenomena. This field emerged in the 19th century particularly through the thinking of thinkers like Auguste Comte, Emile Durkheim, Herbart spencer, Max Weber etc who laid the foundation of modern sociology and social thought.On the other hand Indian Knowledge System or tradition is a broad concept that encompasses a variety of ideas, practices and wisdom passed down from ancient Vedic hymns to modern writings. It includes religious beliefs like, Hinduism, Buddhism, Jainism etc, and philosophical thought, scientific knowledge, arts, culture and spirituality rooted in ancient texts, like the Vedas, Upanishadas, Puranas and more. This study has been attempted to know how Indian Knowledge System embraces holistic perspectives of life; with a deep connection to nature, ethics and self realization.